Gender Mainstreaming und Interkulturelle Öffnung. Design und Ergebnisse einer Evaluation kommunaler Einrichtungen - Göhlich, Michael; Iseler, Katharina (Zeitschrift für Evaluation, 2012)
This paper presents the design of an evaluation in terms of content and methodology. It describes how the evaluation was applied and discusses the findings. We performed the evaluation in the cultural and leisure facilities run by the local authority of a large town in Germany. The evaluation measured the degree of success that had been achieved so far in gender mainstreaming and intercultural opening. We see parallels between the two: in both cases the aim is greater equality (between men and women and between the native German population and immigrants). In both cases it is necessary that organisations should learn. A particular feature of our evaluation is that, as well as studying questions relating to staffing and allocation of resources, we were chiefly concerned with investigating the nature and scope of the cultural programme being provided. This paper presents the evaluation criteria, questions and methods that we developed. We are happy for these to be used by others undertaking similar evaluations in cultural facilities or in other organisations.